Clinical efficacy and mechanism of lymphoplasma exchange in the treatment of Guillain-Barre syndrome - Luo, M-C.; Wang, W-F.; Yin, W-F.; Li, Y.; Li, B-J.; Duan, W-W.; Zeng, Q-M.; Luo, Y-B.; Yang, X-S.; Yang, H. (Cellular and Molecular Biology, 2017)
Guillain-Barre syndrome (GBS) is an autoimmune disease of the nervous system and is the most common acute polyneuropathy. Both cellular and humoral immunity are believed to be involved in the pathogenesis of GBS, and various types of activated CD4+ T cells are thought to orchestrate the onset and progression of GBS. Lymphoplasma exchange (LPE) filtering out activated lymphocytes while exchanging plasma has been used for GBS treatment for years. However the treatment is still not yet optimal. In order to assess the efficacy of this treatment, we evaluate the effect of LPE and determine the appropriate frequency of LPE treatments for GBS patients through comparing the neurological deficit scores and the changes in related immunology indicators of GBS patients before and after LPE treatment. Twenty-four patients with GBS who received LPE were evaluated for immunologic indicants before treatment, on the second day, and the fourth day after the treatment. The immunoglobulin complement and CD4+ T lymphocyte subsets were tested by flow cytometry. The patients’ Medical Research Council sum scores were increased from 25.7±10.4 up to. 36.7±10.4 (P=0.019) and their Hughes scores decreased from 3.7±0.76 to 3.1±0.73 (P=0.027) at 7 days after LPE. In the peripheral blood from patients received LPE treatment, the levels of immunoglobulin, complement, monocytes and fibrinogen were significantly reduced. The percentages of Th1 and Th17 cells in the CD4+ T lymphocyte subsets were significantly decreased, whereas the Th2 and Treg cells were increased in patients after treatment. The changes in CD4+T lymphocyte subsets were correlated with patient MRC score changes. Our data indicate that LPE is effective in treating GBS patients by directly removing immunoglobulin, complement, monocytes, and fibrinogen as well as regulating lymphocyte subsets in the peripheral blood.